The Effect of Crisis Management and Implementation of Health Protocols During the Covid-19 Pandemic On Repurchase Intention With Consumer Safety As Mediation - Fernanda Fernandhytia; Muhamad Wijanarko Prasetyo Hadi; Devie Viera Septiana Sari; Pantri Heriyati (Journal of Business and Management Review, 2022)
The surge of COVID-19 cases has impacted nearly every business sector in DKI Jakarta, including the fast-food restaurant industry, which has suffered a major drop in income. Consumers are becoming selective in choosing fast-food restaurants to visit to avoid the risk of COVID-19 transmission, yet also demand high-quality food with affordable prices and urges the restaurant to implement crisis management and health protocols to maintain consumer safety so that consumers have an interest in revisiting during the pandemic. This study aims to explore the relationship between crisis management, consumer health, and safety protocols to consumer intention in dining in again during the COVID-19 pandemic. The test method used was purposive sampling using PLS-SEM. There were 238 respondents who experienced dine-in at least twice at fast-food restaurants in the international brand franchise category in super-regional and regional malls in Jakarta during the COVID-19 pandemic. The results of this study indicate that crisis management and health protocols have a positive effect on consumer safety and health protocols have a positive effect on repurchase intention, while crisis management has a negative effect. Crisis management and health protocols on repurchase intention mediated by consumer safety also have a negative effect. It is hoped that the research that has been carried out can provide benefits for entrepreneurs in the food and beverages sector, especially fast-food restaurants, with the right strategies in implementing crisis management and health protocols in an effort to maintain consumer safety when dining in during a pandemic similar to COVID-19.